(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines strategies and practices aimed at optimizing the tax burden for economic entities, focusing on ways to reduce tax liabilities while complying with the regulatory and legal framework. It discusses different approaches such as tax planning, taking advantage of benefits and legal structure to minimize the impact of taxes on business. The article also explores the economic implications of effective tax optimization, including the potential to increase competitiveness, improve financial health, and increase investment and growth.